Insulin/carbohydrates ratio during the first 6‐month therapy with insulin degludec in a paediatric population with type 1 diabetes previously treated with insulin glargine. An observational longitudinal study. Issue 2 (12th March 2020) - Tumini, Stefano; Iacono, Olimpia; Comegna, Laura; Fioretti, Elisabetta; Guidone, Paola; Levantini, Gabriella; Panichi, Daniele; Catenaro, Milena; Rossi, Ilaria; Amaro, Flavia; Graziano, Giusi; Rossi, Maria Chiara; et al.
Abstract: Background: No data exist about the changes induced by the transition from first‐generation long‐acting insulins to second‐generation long‐acting analogues in the paediatric population. Objective: To assess changes in insulin/carbohydrate ratio (I:CHO) after the first 6 months of degludec therapy in a paediatric population with type 1 diabetes previously treated with glargine U100. Subjects: All patients treated with degludec under routine clinical practice conditions were retrospectively analysed. Methods: Nonprofit observational retrospective study. Changes during the follow‐up in mean CHO/I ratio were assessed using longitudinal linear models for repeated measures. Rate of hypoglycaemia, ketoacidosis and adverse events was evaluated. Results: Overall, 51 children (mean age 13.8 ± 4.6 years; mean diabetes duration 5.8 ± 3.9 years) started therapy with degludec in the period between April 2017 and April 2018. I:CHO ratio before starting degludec therapy significantly differed among the three meals, being the lowest at breakfast and the highest at dinner. After introducing degludec, I:CHO ratio at lunch (−1.29 95% CI −2.02;−0.57) and at dinner (−3.08 95% CI −4.35;−1.8) significantly decreased, while it slightly increased at breakfast (+1.37 95% CI 0.47;2.28). No episodes of severe hypoglycaemia, ketoacidosis and adverse event were recorded during 6 months. Conclusions: Our data show that the use of degludec is associated with a significant change in the I:CHO ratio at the different meals compared to the previous glargine therapy. This could derive from the flat and prolonged pharmacokinetic profile of degludec. This has important clinical implications for daily insulin dose adjustments. Abstract : No data exist about the changes induced by the transition from first‐generation long‐acting insulins to second‐generation long‐acting analogues in the paediatric population. The study assessed changes in insulin/carbohydrate ratio (I:CHO) after the first 6 months of degludec therapy in a paediatric population with type 1 diabetes previously treated with glargine U100. Our data showed that the use of degludec is associated with a flattening in the I:CHO ratio at the different meals compared to the previous glargine therapy.